Phosphorus recovery as vivianite and amorphous calcium phosphate from high-load industrial wastewater - Randall, Dyllon G.; Jalava, Justus; Vinnerås, Björn; Simha, Prithvi (Frontiers in Environmental Science, 2024)
This study evaluated the recovery of amorphous calcium phosphate and vivianite from industrial wastewater produced by a toothpaste manufacturing facility, where phosphorus concentrations exceed 3,000 mg L−1. The goal was to reduce the phosphorus concentration on-site to below 20 mg P L−1, so that treated wastewater can be discharged to a municipal wastewater treatment plant. In bench-scale experiments, various dosages of Ca(OH)2 (10–25 g L−1) and FeSO4·7H2O (20–60 g L−1) were evaluated to identify optimal conditions for precipitating >99% of the phosphorus. Pilot-scale experiments showed that recovery of amorphous calcium phosphate required dosing 25 g L−1 Ca(OH)2 and mixing for 60 min, whereas recovery of metavivianite required co-dosing 60 g L−1 FeSO₄·6–7H₂O and 7.2 g L−1 NaOH and mixing for 15 min. Variations in influent wastewater composition were found to significantly affect the pH as well as concentrations of residual Fe2+ and Ca2+ in the treated wastewater. Impurities present in chemicals used for precipitating phosphorus were found to influence purity of the recovered phosphate products. The chemical demand for recovering 99% of the phosphorus in the toothpaste industry wastewater was found to be significantly higher than for recovering 95% of the phosphorus in conventional municipal wastewater. This was due to a higher treatment goal and the unique composition of the wastewater, characterised by its high ionic strength and elevated concentrations of Na+ and Cl−, which potentially inhibited nucleation and crystal growth during chemical precipitation. A preliminary economic analysis indicated that recovering vivianite, with potential applications in the electronics industry, could generate significantly higher profits compared to amorphous calcium phosphate, but this depends on the product purity. Overall, this study highlights the potential for industrial wastewater to contribute to a circular phosphorus economy.